VirtARkee floor plan designer and virtual house builder - Alvarez, Paul Richard W. (1997)
The art and science of interior design have been improved throughout the decades, from the invention of the ruler to the development of Computer-Aided Designing (CAD) software. These developments, however, have their focus on speeding up the designing aspect. However, the final products are flat and lack realism. There is a need to improve on the presentation of these designs and make them as realistic as possible in order to appreciate the actual picture they represent. To answer this need, VitARkee was conceptualized, utilizing the power of virtual reality in interior design presentations. VirtARkee evolves from the concept of letting the user design a floor plan which would be used to generate a fully-textured virtual house for him to navigate and explore. VirtARkee is divided into two modules, namely the Floor Plan Expert (VRKedit) and the virtual house builder (VRKgen). The Floor Plan Expert is a user-friendly guide in constructing the floor plan, with pre-defined rooms, furniture, and fixtures to choose from. These are placed in the design window, thus creating a single-level, two dimensional floor plan. Upon saving the floor plan created, an output file is produced. The Virtual House Builder then interprets this output file to generate the corresponding virtual house, a three-dimensional world navigated in real-time by the user using the mouse. VirtARkee was implemented using Borland C++ for Windows and the RenderWare Real-Time 3D Graphics Library for Professionals by Criterion.